Reducing radiation-related morbidity in the treatment of nasopharyngeal carcinoma. (February 2017) - Chan, Jason W; Parvathaneni, Upendra; Yom, Sue S
While radiation therapy is the mainstay of treatment for nasopharyngeal carcinoma, the anatomic location of the nasopharynx in close proximity to radiation-sensitive organs such as the salivary glands, optic nerves and chiasm, cochlea, brainstem and temporal lobes presents a special challenge. Technological approaches to reducing the morbidity of nasopharyngeal cancer irradiation have been historically successful with the evolution from 2D techniques to increasingly conformal forms of radiation therapy. This report reviews normal tissue dose constraints and major considerations in target delineation for patients with nasopharyngeal cancer in the intensity-modulated radiation therapy era. Furthermore, this report discusses more contemporary approaches to toxicity reduction such as the judicious reduction or omission of radiation to low-risk regions and the potential role of particle beam therapy.